Analisis perilaku deformasi Bendungan Bili-Bili dengan metode penilaian berdasarkan data instrumentasi pada tubuh Bendungan Bili-Bili - Makmur, Abdul; Musa, Ratna; Sar, Mas ud (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This research aims to analyze behavior at the Bili-Bili Dam based on instrumentation data collected from the construction period to operation. The data used includes the results of measurements of horizontal deviation, changes in vertical height, and pore air pressure obtained through instruments such as sliding stakes, piezometers, and auto levels. The main focus of the research is to identify changes over time, address dam stability, and provide recommendations for mitigating the risk of structural failure. This research method involves collecting secondary data from measurement records from 1997 to 2023. Analysis was carried out using permit acceptance criteria based on ICOLD (International Commission on Large Dams) standards. The results of horizontal deviation measurements show that the largest movement occurs at the top of the dam, but is still within the design tolerance limits. Vertical measurements show the greatest elevation decrease (subsidence) in the central part of the dam, which remains in line with initial predictions based on geotechnical parameters. Meanwhile, pore water pressure measured via a piezometer shows a normal decrease in accordance with changes in reservoir water level. The research results showed that the freezing that occurred was mostly caused by consolidation of the rock fill material and hydraulic interactions between the water reservoir and the dam structure. However, several areas show anomalies that require further monitoring, especially on the left and right wings of the dam. In conclusion, the Bili-Bili Dam is still in a stable and safe condition. Recommendations include increased monitoring of area anomalies and strengthening the routine maintenance program to maintain long-term stability..